(untitled) (ModaPalavra e-periódico, 2019)
This research aims to analyze the artistic aspects of Portuguese tiles as one of the main sources of inspiration in the development and planning of contemporary fashion collections. Specifically, it addresses the art of tile as one of the most important means of developing Ceramic Design and briefly analyzes its history and origins. It also analyzes the Textile Design, in special the textile printing sector, as an area of development of Surface Design, showing the tiles, through the Ceramic Design, as a source of inspiration in several creative processes with regard to the production of new products linked to the Textile and Fashion market in contemporary times.